2020
DOI: 10.1007/s42486-020-00026-2
|View full text |Cite
|
Sign up to set email alerts
|

Feature learning for Human Activity Recognition using Convolutional Neural Networks

Abstract: The use of Convolutional Neural Networks (CNNs) as a feature learning method for Human Activity Recognition (HAR) is becoming more and more common. Unlike conventional machine learning methods, which require domain-specific expertise, CNNs can extract features automatically. On the other hand, CNNs require a training phase, making them prone to the cold-start problem. In this work, a case study is presented where the use of a pre-trained CNN feature extractor is evaluated under realistic conditions. The case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…[ 6 , 7 , 8 , 9 , 10 , 11 ]. DCNNs are now widely used for the development of automatic human activity context recognition [ 6 , 7 , 8 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Representational learning of activity context from raw sensor data using a DCNN has been proposed for automatic feature extraction in activity context recognition [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 , 7 , 8 , 9 , 10 , 11 ]. DCNNs are now widely used for the development of automatic human activity context recognition [ 6 , 7 , 8 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Representational learning of activity context from raw sensor data using a DCNN has been proposed for automatic feature extraction in activity context recognition [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, deep learning algorithms have the capability for unsupervised and incremental learning because of its deep network structure compared to the traditional neural network. A DCNN is composed of multiple building blocks, such as convolutional layers, pooling layers, and fully connected layers [ 9 , 13 , 14 , 15 , 16 , 17 ]. It has been designed to automatically and adaptively learn spatial hierarchies of features, from low to high-level patterns, through backpropagation algorithm [ 16 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In [27], it was shown that the CNN model could extract a suitable internal structure to produce deep features automatically and outperform state-of-the-art methods on real-world datasets. CNN architectures, unlike other feature-based models, do not require sophisticated feature engineering [28][29][30]. These papers provided supportive results and reviews showing that 1D CNN could be used as an automatic feature extraction mechanism for one-dimensional data.…”
Section: Introductionmentioning
confidence: 88%
“…Unlike neural networks with a single hidden layer NN, CNN are able to learn how to extract more detailed features as its depth increases. Being based on the visual cortex, CNN models are commonly used in image-based applications, but have also been used in inertial sensor-sensor based applications such as activity recognition [ 31 ] and the detection of Parkinson’s disease-related events [ 32 , 33 ]. In such cases, instead of using an image input, the input is typically replaced by a 2D ( n × m ) matrix containing n samples from m inertial sensor signals.…”
Section: System Overviewmentioning
confidence: 99%